Guía metodológica para la implementación de la Norma NTC 6001:2017 en Tebioder S.A.S Tecnología Biodegradable, mipyme dedicada a la maquila de productos biodegradables en higiene personal y productos de aseo en Cartagena de Indias. (2022)
The purpose of this document is to build a management system for the family microenterprise of TEBIODER S.A.S BIODEGRADABLE TECHNOLOGY that was born on April 19, 2021, through the NTC 6001: 2017 standard "Management system for micro and small businesses (MYPES)” which will allow the organization establish the fundamental minimum requirements to comply with the requirements of the market; thus generating results in its sustainability, taking into account factors such as innovation and business survival.